Trophic ulcers in the carpal tunnel syndrome - Abelardo Q.-C. Araújo; Henrique Barros Neto; Henrique Bulcão; Osvaldo J. M. Nascimento (Arquivos de Neuro-Psiquiatria)
A patient with carpal tunnel syndrome (CTS) and trophic ulcers is described. Despite the healing of the ulcers after surgery for CTS, the severe sensory deficit and the electrophysiological tests have not shown any significant improvement. We think these findings argue against the hypothesis of the sensory deficit being responsible for the trophic ulcers. We favor a major role for the sympathetic disturbances as the main cause for those lesions.